Hybrid Issuance Regimes for Corporate Bonds in Emerging Market Countries : Analysis, Impact and Policy Choices - Loladze, Tamar (World Bank, Washington, DC, 2015)
Securities regulators in many developing countries are looking for ways to help grow their nongovernment bond markets to finance development. A common challenge is onerous regulations for issuance of bonds, which tend to discourage companies from coming to market. This paper explains and analyzes an issuance framework—a hybrid offer regime (HBOR)—that is particularly suitable for bonds and could help encourage greater issuance and market growth. The HBOR reduces issuance requirements and approval times for bond issuers but maintains certain protections to ensure investor comfort. While certain aspects of this type of issuance have been covered in literature on private placements, the review of hybrid offer regimes, as discussed in this paper, is new and has been evaluated by the WBG. Drawing on the experience of eight countries, the paper identifies key features of HBORs and highlights important issues for policymakers to consider in their implementation. The findings conclude that the most salient features of HBORs are: i) investment limited to qualified investors, usually institutional and/or high net worth; ii) reduced initial and ongoing disclosures, including exemption from a full prospectus; iii) limited role of the regulator, if any, in the approval process; iv) unrestricted access to secondary market trading for eligible investors; and v) continued provision of antifraud protections against false/misleading statements in disclosures. The paper also looks at issuance trends in three countries and finds that the HBOR may have had a positive impact on encouraging new, less established issuers to come to the bond market.